Análisis de la cocina tradicional para fortalecer la identidad cultural de la parroquia San Luis, cantón Riobamba - Morocho León, Jenifer Dayana (2026)
The research was based on an analysis of traditional cuisine to strengthen the cultural identity of the San Luis parish, Riobamba canton. The problem identified focuses on the trend of cultural identity loss, with weak interest in traditional cuisine threatening to undermine cultural identity in the San Luis parish. The aim is to analyze the relationship between traditional cuisine and the strengthening of cultural identity in the parish of San Luis, Riobamba canton. The research was conducted using a mixed methodology. To achieve a more complete understanding of the study, surveys were conducted among the population of San Luis to identify their profile and opinions, and interviews were conducted with representatives of the parish and adults who have more knowledge about the subject of the study. The findings indicate that most of the population 81.8% believe that the transmission of ancestral culinary knowledge among the inhabitants of the San Luis parish is very important. Likewise, 82.4% mention that it is very important to recognize the influence of historical events on the identity of their parish. In addition, it is recommended that the leaders of the parish council document and preserve traditional cuisine recipes to keep alive the recipes that were traditionally prepared in the parish using local ingredients, thus maintaining the cultural identity of the San Luis parish.